Decoupling Institutional Pressure on Green Supply Chain Management Efforts to Boost Organizational Performance: Moderating Impact of Big Data Analytics Capabilities - Shahzad, Fakhar; Du, Jianguo; Khan, Imran; Wang, Jian (Frontiers in Environmental Science, 2022)
This paper aims to empirically examine the impact of institutional pressure on green supply chain management (GSCM) efforts and the moderating role of big data analytics capabilities (BDAC) on organizational performance. This study greatly develops a research model by integrating institutional theory, the natural resource-based view (NRBV), and dynamic capability theory to explore this relationship. This article is based on structured questionnaire data of 347 supply chain personnel. We employed structural equation modeling to verify the research hypotheses. The findings provide empirical support for institutional pressures affecting GSCM efforts and organizational performance. The results also showed that the moderating effect of BDAC positively strengthened the impact of GSCM effort on organizational performance. The findings extend and refine the existing GSCM literature, providing new insights for scholars to explore this view further. Practitioners can turn their attention to incorporating institutional pressures and advanced technologies into organizational decision-making, even in times of crisis such as Covid-19.